Is diabetes knowledge associated with health-related quality of life among subjects with diabetes? A preliminary cross-sectional convenience-sampling survey study among English-speaking diabetic subjects in Singapore - Zhang, X.-H. (2014)
Journal of Chinese Clinical Medicine